Mobile Infrastructure and Rural Business Enterprises : Evidence from SIM Registration Mandate in Niger - Annan, Francis (World Bank, Washington, DC, 2017)
Business enterprises and non-agricultural startups in rural economies play crucial roles in ending the vicious cycle of poverty. The propagation of business enterprises are, however, subject to a high degree of institutional frictions and vacuums e.g., information; but mobile infrastructure which has the externality of flowing information can help overcome most of these vacuums through reduced fixed costs, lower cost of information or search, and outreach to a broader customer base. This paper studies the effects of mobile infrastructure ("mobile use activity") on propagation of rural business enterprises in Niger. Instrumental variable estimates exploit the exogenous introduction of the 2013 national mandatory SIM registration reform which provides a quasi-experimental set-up for mobile use and activity. The mandate deactivated about one-third of all existing prepaid SIMs and led to a remarkable decline in mobile use activity. The results suggest that there is economically substantial effect of mobile infrastructure on propagation of business enterprises. Moving a household with mobile use activity to a no mobile use activity environment due to SIM deactivation results in roughly 33.1 percent points decline in the likelihood of engaging in non-agricultural business enterprises. Most of this effect come from three major sources: households' ownership of a business service or center; ownership of small income generating activities; and involvement in the transformation of agricultural products. There is suggestive evidence that the reform's impact is disproportionately larger for women. With the expansion of mandatory SIM registration reforms in developing countries, the findings have extended implications in these contexts.